2012
DOI: 10.1007/s10549-012-2260-9
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of IGF1R and phosphorylated IGF1R as targets in HER2-positive breast cancer cell lines and tumours

Abstract: Insulin-like growth factor-1 receptor (IGF1R) signalling is implicated in resistance to trastuzumab. However, the benefit of co-targeting HER2 and IGF1R has not been extensively studied, and the relationship between activated IGF1R and clinical response to trastuzumab has not been reported. This study aimed to evaluate the combination of trastuzumab with IGF1R tyrosine kinase inhibitors (TKIs) in a panel of HER2-positive breast cancer cell lines, and to examine the relationship between IGF1R expression and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…In recent years, IGF1R activity has been shown to play a role in driving HER2 therapy trastuzumab resistance, and co-targeting HER2 and IGF1R is thought to be a viable therapeutic approach to overcome resistance (Browne et al 2012). Mechanisms associated with IGF1R-driven HER2 therapy resistance are not well defined; however, there are studies suggesting that it is mediated via de-regulation of the PTEN/PI3K/AKT signaling pathway (Gallardo et al 2012).…”
Section: Her2 Amplified Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, IGF1R activity has been shown to play a role in driving HER2 therapy trastuzumab resistance, and co-targeting HER2 and IGF1R is thought to be a viable therapeutic approach to overcome resistance (Browne et al 2012). Mechanisms associated with IGF1R-driven HER2 therapy resistance are not well defined; however, there are studies suggesting that it is mediated via de-regulation of the PTEN/PI3K/AKT signaling pathway (Gallardo et al 2012).…”
Section: Her2 Amplified Breast Cancermentioning
confidence: 99%
“…Thus, co-targeting strategies using Src inhibitors in conjunction with HER2-targeted therapies may be clinically effective for HER2-amplified cancers to eliminate IGF1R-mediated HER2 therapy resistance (Browne et al 2012). At present, there are no clinical trials testing this type of combination therapy for breast cancer; however, a phase 2 trial testing the safety of IMC-A12 and the Src inhibitor, sorafenib, in combination for advanced liver cancer may give some further insight into the potential of combination therapy (Tables 1 and 2: Ref #27, NCT00906373).…”
Section: :11mentioning
confidence: 99%
“…A study that utilized the same polyclonal antibody as our study (directed against the β subunit of IGF1R) showed that 65% of 297 unselected breast cancers did not have IGF1R protein expression and 3% of the cases had 3+ staining(39). This same antibody detected membrane IGF1R (when exceeded cytoplasmic staining) in 13.8% of 160 HER2+ breast cancers(25). In addition, our results are in alignment with recent findings that demonstrated that IGF1R protein expression was associated with HER2-negativity, and reduced IGF1R expression (compared to moderate expression observed in normal breast epithelial elements) was observed consistently in ER−/PR−/HER2+ breast tumors(38).…”
Section: Discussionmentioning
confidence: 93%
“…IGF1R has been linked to resistance to chemo/hormonal/biological/radio-therapy(19) and particularly implicated in therapeutic resistance to trastuzumab(8, 20, 21). Preclinical evidence has demonstrated that increased IGF1R signaling interferes with trastuzumab action(8, 22, 23), and synergy has been observed between trastuzumab and anti-IGF1R agents in inhibiting HER2+ tumor cell growth(24, 25). A unique interaction/heterodimerization of IGF1R and HER2 has been observed in trastuzumab-resistant cells but not in sensitive parental cells (2628).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation